The Psychology and Neuroscience of Financial Decision Making. Issue 9 (September 2016) - Frydman, Cary; Camerer, Colin F.
Abstract : Financial decisions are among the most important life-shaping decisions that people make. We review facts about financial decisions and what cognitive and neural processes influence them. Because of cognitive constraints and a low average level of financial literacy, many household decisions violate sound financial principles. Households typically have underdiversified stock holdings and low retirement savings rates. Investors overextrapolate from past returns and trade too often. Even top corporate managers, who are typically highly educated, make decisions that are affected by overconfidence and personal history. Many of these behaviors can be explained by well-known principles from cognitive science. A boom in high-quality accumulated evidence–especially how practical, low-cost 'nudges' can improve financial decisions–is already giving clear guidance for balanced government regulation. Trends: A boom in accumulated evidence over the past several decades shows that financial decision-making at all levels in the economy often departs from the predictions of models of rational information-processing New data from a variety of sources, including the human brain, corporate conference calls, genetics, and online trading activity, allow researchers to uncover new facts about the cognitive processes that influence financial decision-making Evidence from these new data sources, and vigorous randomized field experiments, are already being used for prescriptive purposes to test out low cost practical "nudges" by governments around the world Closer collaboration between behavioral economic theory and methodologies from cognitive science is likely to generate important new insights on financial decision-making from households to corporate managers